A PERSPECTIVE ON JUSTIFYING THE UKRAINE - RUSSIA WAR. ELEMENTS OF PROPAGANDA - Gabriela-Cătălina DANCIU (Association of Social and Educational Innovation, 2023)
This article represents a deep dive research into communication aspects that induce the justification and maintenance of the war in Ukraine (2022) using propaganda elements. We are witnessing an ongoing conflict, and we don't know how it will end, what the international implications will be, how the behaviors of the great powers will change, or what the small countries will do. I focused my research of this article on two relevant events. The first event is external and has a diplomatic nature (the Munich International Security Conference), and the second one is internal and concerns the legal nature of the phenomenon (the Ukrainian regulations on the Law of Minorities). I examined these two events through communication channels and message transmission perspectives. I put together arguments on how the belligerent states (Russia and Ukraine) are both focused on a permanent win.